Frontal cortex and reward-guided learning and decision-making. - Rushworth, M; Noonan, M; Boorman, E; Walton, M; Behrens, T (2011)
Reward-guided decision-making and learning depends on distributed neural circuits with many components. Here we focus on recent evidence that suggests four frontal lobe regions make distinct contributions to reward-guided learning and decision-making: the lateral orbitofrontal cortex, the ventromedial prefrontal cortex and adjacent medial orbitofrontal cortex, anterior cingulate cortex, and the anterior lateral prefrontal cortex. We attempt to identify common themes in experiments with human participants and with animal models, which suggest roles that the areas play in learning about reward associations, selecting reward goals, choosing actions to obtain reward, and monitoring the potential value of switching to alternative courses of action.